2018
DOI: 10.1021/acs.jafc.8b01181
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Phenolic Compounds in Black Walnut Kernels

Abstract: Black walnuts ( Juglans nigra L.) are highly valued for producing phenolic-enriched nuts. The objectives of this study were to identify and characterize the phenolic contents of 11 different black walnut cultivars and compare the levels of these phenolics between black walnuts and English walnut ( Juglans regia L.). Totally, 16 phenolics including phenolic acids, flavonoids, and catechins were identified in the black walnut kernels, with ellagic acid predominating over the other phenolics. Significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…It is likely that the loss of the BBE gene family in J. regia and J. sigillata occurred in the Dioscaryon ancestor, but that does not eliminate the possibility that these species were favored and therefore selected for their potentially tamed secondary metabolite profiles. Until recently, chemical analyses in Juglans have been limited to observational studies and comparisons of different cultivars within a species (Vu et al , , ). Additional studies contrasting metabolomic profiles of domesticated species with their wild relatives will offer valuable insight into tree domestication, especially when paired with genome annotations.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the loss of the BBE gene family in J. regia and J. sigillata occurred in the Dioscaryon ancestor, but that does not eliminate the possibility that these species were favored and therefore selected for their potentially tamed secondary metabolite profiles. Until recently, chemical analyses in Juglans have been limited to observational studies and comparisons of different cultivars within a species (Vu et al , , ). Additional studies contrasting metabolomic profiles of domesticated species with their wild relatives will offer valuable insight into tree domestication, especially when paired with genome annotations.…”
Section: Discussionmentioning
confidence: 99%
“…Two different commercially available botanical formulations which contain Juglans nigra were also recently shown to have activity against log phase spirochetes of B. burgdorferi strain GCB726, round bodies and biofilm formation in in vitro testing (86). This current study adds to the research on the potential anti Borrelia activity of Juglans nigra which has been shown to have several constituents (87) with antimicrobial properties including juglone (5-hydroxy-1,4-naphthalenedione), phenolic acids, flavonoids, and catechins (including epigallocatechin gallate) (8893). Further studies are needed to elucidate which constituents have anti-borrelial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two different commercially available botanical formulations which contain Juglans nigra were also recently shown to have activity against log phase spirochetes of B. burgdorferi strain GCB726, round bodies and biofilm formation in in vitro testing (64). Juglans nigra has also been shown to have multiple constituents (65) with antimicrobial properties including juglone (5-hydroxy-1,4naphthalenedione), phenolic acids, flavonoids, and catechins (including epigallocatechin gallate) (66,67). Further studies are needed to elucidate which constituents have anti-borrelial activity.…”
Section: Discussionmentioning
confidence: 99%